Revealing the Potency of Camelia sinensis and Serenoa repens as Purinoreceptor Inhibitor for Benign Prostatic Hyperplasia Treatment through in Silico Study - Putra, Mega Memory Rahasa; Seputra, Kurnia Penta (Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Benign prostatic hyperplasia (BPH) is the most common prostate disease in elderly men that leads to a significant deterioration in patients' quality of life (QoL). Pharmacological therapy of 5-alpha reductase inhibitor and alpha adrenoreceptors blocker often causes several side effects that decrease the QoL, so it is necessary to develop a new treatment for BPH. Purinoreceptor is a novel receptor that can inhibit electrically evoked nerve-mediated contractions in the prostate. Tea leaves (Camellia sinensis) and Saw palmetto (Serenoa repens) are herbs that have potential as alternative therapies for BPHObjective: to reveal the mechanism of Camellia sinensis and Serenoa repens through purinoreceptor and the other receptorsMethods: Structures of active compounds were extracted from PubChem and protein from PBD. The active compounds Camellia sinensis and Serenoa repens to the target protein purinoreceptors, 5-alpha-reductase, and alpha adrenoreceptors was evaluated in silico using a docking server with Finasteride dan Tamsolusin as a control. Molecular docking method using dockingserver application.Results: Epigallocatechin gallate only compound that has potency in blocking purinoceptors and 5-alpha-reductase. Capric acid, Caprylic acid, Lauric acid, Linoleic acid, and Myristic acid have the potential to bind to alpha adrenoreceptor ligands.Conclusion: Camellia sinensis have potential and effects as alternative therapies in benign prostatic hyperplasia on the target protein purinoreceptors, 5-alpha-reductase, and alpha adrenoreceptors. But, Serenoa repens have potential only through alpha adrenoreceptors.